(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to assess the knowledge, attitude, and practice (KAP) of patients after surgery for ingrown toenail (onychocryptosis) with two specific objectives: (1) to describe the clinical characteristics of patients with ingrown toenail, and (2) to evaluate their KAP regarding postoperative wound care. Methods: A pre–post intervention study was conducted on 100 patients at the National Hospital of Dermatology and Venereology from April 1, 2024 to April 1, 2025. The questionnaire included five parts: general information, knowledge (10 questions), attitude (5 questions), practice (5 questions), and support needs (3 questions). Data were analyzed using SPSS 20.0 and R 4.1.0. Results: Before intervention, the proportion of patients with adequate KAP was limited (good knowledge: 5%, positive attitude: 6%, good practice: 33%). After intervention, mean scores improved significantly: knowledge increased from 3.97±2.29 to 7.71±1.26, attitude from 18.01±1.57 to 22.81±1.66, and practice from 3.12±0.88 to 4.21±0.74 (p<0.05). Additionally, 84% of patients expressed a need for remote postoperative support. Conclusion: Health education intervention significantly improved KAP regarding postoperative wound care in patients undergoing ingrown toenail surgery. Integrating remote counseling and instructional videos is recommended to enhance the sustainability of the intervention.